A study on quantum theory in accordance with Islamic science - Ab. Nasir Jaafar (International Institute of Islamic Thought and Civilisation (ISTAC), International Islamic University Malaysia, 2016)
Metaphysical methods based on the Qur'an and relevant Islamic science principles have been extensively used to expose the mysterious quantum world by providing detailed explanations on some of the important phenomena observed in the quantum world, particularly on the wave-particle duality. This metaphysical approach provides an alternative to complement the mathematical rigour usually employed in empirical studies. The scientific analysis of the relevant verses coupled with the scientific findings indicate that each element of an atom consists of electric charges and a permanent magnet, in addition to the presently known induced magnetism due to the spin of an element such as the electron. New mathematical equations are derived to calculate the postulated potential energy, and the ratio of the proposed permanent or static magnetic fields and the induced one. Other relevant equations derived include the calculation of electromotive force and the exhibition of wave-particle duality. The relevant verses are also interpreted scientifically to exhibit the space and time relation as a pair, and to expose philosophically how time dimension creates consciousness. Lastly, the new theory is comprehensively substantiated by revealing its significant role in providing some explanations on fundamental issues that relate to zero point energy and the origin of mass. It is found that the theory has comfortably accomplished the task. Islamic science thus has proven that religion can contribute to the advancement of science, particularly in the exploration of the quantum world.